System instytucjonalny w procesie rozwoju obszarów wiejskich - Kołodziejczyk, Danuta (The Institutional System in the Process of Rural Areas Development, 2005)
The paper discusses the influence of the institutional system on the development of rural areas. The importance of the system for the development of such areas is determined by its role in the innovation process. The study shows, there are few institutions in agribusiness area related to the market that could help to introduce a new product into the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 450-455